Serum folate concentrations, asthma, atopy, and asthma control in Peruvian children. (December 2017) - Nicholson, Andrew; Pollard, Suzanne L.; Lima, John J.; Romero, Karina M.; Tarazona-Meza, Carla; Malpartida-Guzmán, Gary; Mougey, Edward; Hansel, Nadia N.; Checkley, William; ,
Abstract: Background: The relationship between folate status and asthma-related outcomes has not been carefully examined in low- and middle-income countries where folate deficiency is common. Methods: Ancillary analysis of an unmatched case-control study in which we analyzed serum folate concentrations in 412 children with asthma and 342 controls living in peri-urban communities in Lima, Peru. We examined baseline associations between folate and asthma, atopy, total serum IgE, pulmonary function, and fractional exhaled nitric oxide. We then followed children with asthma longitudinally for 6–9 months and assessed associations between folate and odds of uncontrolled asthma (defined as Asthma Control Test score ≤ 19) and of ≥1 emergency visits during follow-up. Results: A 10 ng/mL decrease in serum folate was associated with 45% higher adjusted odds of asthma (OR = 1.45, 95% CI 1.05–2.02). The folate-asthma relationship differed by atopic status: a 10 ng/mL decrease in serum folate was associated with a 2.4-fold higher odds of asthma among children without atopy (2.38, 1.20–4.72) and 23% higher odds of asthma in children with atopy (1.23, 0.85–1.80). Among children with asthma, a 10 ng/mL decrease in serum folate was associated with 62% higher odds of uncontrolled asthma (1.62, 1.02–2.56) and 73% higher odds of ≥1 emergency visits during follow-up (1.73, 1.05–2.85). Conclusions: Serum folate concentrations were inversely associated with asthma, but this effect was stronger in children without atopy. Among children with asthma, lower serum folate concentrations were associated with higher risk of uncontrolled asthma. Highlights: Lower serum folate concentration is associated with a higher odds of asthma. We observed a stronger effect for this relationship in children without atopy. Lower serum folate concentrations were associated with worse asthma control. A threshold for the association of circulating folate with asthma is proposed.